Efficacy of MCU-based and 3D-FEA for Improving Cervical Spondylosis - Meigui KE; Ruixu XU; Ningying HUANG; Hai GUO; Xinghui YAN; Nanxi WU; Sidong DOU (康复学报)
Objective:Based on the Muli-Cervical Unit(MCU)and three-dimensional finite element analysis(3D-FEA),this study explored whether the"Tuo tian zhuang"exercise in the Southern Shaolin Yi Jin Jing can improve the efficacy of electroacupuncture in the treatment of cervical spondylosis.Methods:Patients who met the inclusion criteria for cervical spondylosis of cervical type were randomized assigned by age stratification into control group and experimental group. A total of effective cases were 156 with 78 cases in each group. Both the control group and the experimental group were treated with electroacupuncture for 4 weeks, and the experimental group was continued to practise the Southern Shaolin Yi Jin Jing"Tuo tian zhuang"exercise for 12 weeks. A finite element model, the visual and analogue scale(VAS)of pain and MCU were used to compare the pain changes, including cervical spine mobility in all directions, disc stress between C4-C7during forward flexion and joint capsule stress in the hooks of the two groups before and after treatment.Results:After 4 weeks of electroacupuncture treatment, the VAS scores of both groups were improved significantly compared with scores before treatment(P<0.05), with no significant differences between the ages groups within the group and the subgroups between the groups(all P>0.05). After 12 weeks of treatment, VAS scores were lower in the experimental group and in all subgroups than in the control group(P<0.05 and P<0.017, respectively);and there was a statistical difference in the degree of pain relief in each age subgroup(P<0.05), suggesting that young patients had better pain relief than middle-aged and elderly patients. Patients in both groups showed varying degrees of increase in cervical mobility and muscle strength in all directions(P<0.05), 12 weeks of treatment with significant differences between the experimental and control groups and between subgroups(P<0.05 and P<0.017, respectively);the C4-C7disc stress and C4-C7crotal joint capsule stress were reduced to varying degrees between age subgroups compared to the pre-treatment period in this group. The stresses in the C4-C7 disc and C4-C7capsular joint were reduced to varying degrees between the ages subgroups compared with those before treatment(P<0.05).Conclusion:The combination of electroacupun-cture with the Southern Shaolin Yi Jin Jing"Tuo tian zhuang"is more effective than electroacupuncture alone in relieving pain, impro-ving the mobility of the cervical spine, improving muscle strength and reducing stress in the cervical. The young group of patients have the best therapeutic effect.